Akuntabilitas dan Transparansi dalam Pelayanan Publik : Studi Kasus Pelayanan KTP dan KK di Kantor Dispendukcapil Jember - Tri Nur Fadhilla (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This study aims to examine the accountability and transparency of public services regarding the issuance of Resident Identity Cards (KTP) and Family Cards (KK) at the Jember Population and Civil Registration Agency (Dispendukcapil). The findings reveal a gap between policy and actual implementation regarding accountability and transparency. This gap requires serious attention from the Jember Regency Dispendukcapil to improve service quality. While accountability and transparency measures have been implemented in the KTP and KK issuance process, they are not yet optimal. Interview findings indicate that although Standard Operating Procedures (SOPs) are available on the official Jember Dispendukcapil website, 70% of applicants are unaware of this. This situation demonstrates that the transparency aspect—specifically regarding information disclosure—is not functioning effectively. Despite the availability of information channels, efforts to disseminate this information to the public, particularly in remote areas, remain insufficient. Improvements could begin with strengthening human resources, upgrading facilities and infrastructure, and intensifying public outreach. These measures are expected to make the KTP and KK issuance process faster, more accurate, and more accountable. Ultimately, achieving good local governance will bring the administration closer to meeting public expectations.
Finalisasi 1 Juli 2026_Yudi
Keywords: Akuntabilitas; Transparansi; Pelayanan Publik